2017
DOI: 10.1200/jco.2017.35.15_suppl.3522
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor DNA (ctDNA) utilizing a high-sensitivity panel to detect minimal residual disease post liver hepatectomy and predict disease recurrence.

Abstract: 3522 Background: Preliminary data suggests that ctDNA can serve as a marker of minimal residual disease following colorectal cancer (CRC) tumor resection. Applicability of current ctDNA testing is limited by the requirement of sequencing known individual tumor mutations. We explored the applicability of a multi-gene panel ctDNA detection technology in CRC. Methods: Plasma was prospectively collected from CRC patients (pts) undergoing hepatic resections with curative intent between 1/2013 to 9/2016. In a blind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 0 publications
2
22
0
1
Order By: Relevance
“…Molecular Residual Disease (MRD). ctDNA has been shown in multiple tumor types to detect MRD, including nasopharyngeal carcinoma (27), colorectal carcinoma (28)(29)(30)(31)(32), locally advanced rectal carcinoma (33), breast carcinoma (34), pancreatic carcinoma (35,36), and lung carcinoma (37) ( Table 1). ctDNA in the plasma has a short half-life (<2 hours); however, it has been found that ctDNA may be elevated 24 hours following intervention in early post-operative samples, most likely due to release of ctDNA from damaged tissue (28).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular Residual Disease (MRD). ctDNA has been shown in multiple tumor types to detect MRD, including nasopharyngeal carcinoma (27), colorectal carcinoma (28)(29)(30)(31)(32), locally advanced rectal carcinoma (33), breast carcinoma (34), pancreatic carcinoma (35,36), and lung carcinoma (37) ( Table 1). ctDNA in the plasma has a short half-life (<2 hours); however, it has been found that ctDNA may be elevated 24 hours following intervention in early post-operative samples, most likely due to release of ctDNA from damaged tissue (28).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Yao et al noted RAS/BRAF mutation status in ctDNA as a prognosticator of poor progression free survival (PFS) in metastatic CRC patients treated with first line therapy, as has been well characterized in tumor genomic analysis [43,44]. These results reflect those of other studies examining the prognostic significance of detectable mutations in CRC ctDNA [35,37,43,45]. Circulating tumor DNA in CRC has also been shown to be effective in monitoring disease recurrence after completion of all treatments, further exemplifying its prognostic value.…”
Section: Liquid Biopsy As a Prognostic Toolmentioning
confidence: 56%
“…Liquid biopsy as a tool for monitoring disease recurrence has also been well studied and the use of serial profiling has allowed for detection of recurrence up to 6 months before radiological imaging in CRC and pancreatic cancer patients [29,35,36]. For metastatic CRC, recent studies [34,35,37] demonstrate a decline and subsequent rise in ctDNA levels in response to chemotherapy and acquisition of resistance respectively, indicating that longitudinal monitoring of ctDNA may provide an alternative to the measurement of blood tumor markers, which often lack sensitivity and specificity [38]. Investigations on ctDNA for pancreatic cancer show similar findings, with changes in ctDNA corresponding closely with radiological imaging, CA19-9 levels, and recurrence [29,36].…”
Section: Liquid Biopsy As a Diagnostic Toolmentioning
confidence: 99%
“…It was previously reported that, in patients who underwent complete surgical resection, postoperative detection of ctDNA significantly correlated with RFS ( P = 0.002, HR 3.1; 95% CI 1.7–9.1) and recurrence was detected in ctDNA a median of 5.1 months before radiographic recurrence [ 13 ]. In our study, we explored factors that might relate to recurrence after primary tumor resection.…”
Section: Discussionmentioning
confidence: 99%